Terapi non farmakologi jus buah nanas terhadap keputihan pada wanita - Hasanah, Uswatun (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2024)
IntroductionPineapple juice is known to have antibacterial properties that become more potent with higher concentrations. One of its active components, the enzyme bromelain, also functions as a natural antiseptic. This study aims to determine the effectiveness of pineapple juice in treating vaginal discharge among women in Kelurahan Jalur Mulya, under the jurisdiction of Puskesmas Tirtaharja, Muara Sugihan District, Banyuasin Regency. MethodsThis study employed a quasi-experimental design with two groups: an intervention group and a control group. The independent variable was the administration of pineapple juice, while the dependent variable was the occurrence of vaginal discharge. A total of 100 respondents participated, divided equally into 50 in the intervention group and 50 in the control group. Data were analyzed using the Chi-square statistical test. ResultsThe analysis showed an Asymp. Sig (2-tailed) value of 0.602. Since this value is greater than 0.05, the null hypothesis is accepted. This indicates that pineapple juice does not have a statistically significant effect in treating vaginal discharge among the women studied. Conclusion and RecommendationsBased on the findings, pineapple juice is not recommended as a treatment for vaginal discharge during active symptoms. However, it is also not identified as a food that triggers the condition, making it safe to consume under normal circumstances. These results are expected to serve as a reference for the public in making informed dietary choices when experiencing mild reproductive health issues such as vaginal discharge.